Efficacy of non-pharmacological interventions for depression in individuals with Parkinson's disease: A systematic review and network meta-analysis - Wang, Yuxin; Sun, Xue; Li, Fei; Li, Qi; Jin, Yi (Frontiers in Aging Neuroscience, 2022)
Background Depression in Parkinson's disease (PD) is a major health concern worldwide. Recently, an increasing number of non-pharmacological interventions have been used in PD to alleviate depressive symptoms. However, it is uncertain which intervention is the best, and related evidence is limited. This network meta-analysis was performed to compare and rank non-pharmacological interventions for PD and analyze their effects on depression to provide evidence for clinicians to choose appropriate non-pharmacological management options. Methods The PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO, China National Knowledge Infrastructure (CNKI), and Wanfang databases were searched from inception to April 7, 2022. Two authors screened all studies, extracted the data, and evaluated the methodological quality. STATA software version 16.0 was used to conduct the network meta-analysis. Results Our network meta-analysis included 62 studies involving 3,050 participants and 35 non-pharmacological interventions. Although most non-pharmacological interventions showed non-significant effects, the surface under the cumulative ranking curve (SUCRA) values indicated that the best non-pharmacological intervention for depression was dance (82.3%), followed by LSVT-BIG therapy (77.4%), and CBT (73.6%). Conclusion Dance can be considered as an effective therapy for improving depression in patients with PD. In the future, more strictly designed trials are needed to verify the conclusions of this network meta-analysis.